Is mathematics still scary? Primary school pupils' perceptions of mathematics - Mubarik; Ibnu Hadjar; Welli Meinarni; Annisa Dwi Kurniawati (Riemann: Research of Mathematics and Mathematics Education, 2026)
For a long time, research has shown that mathematics is an unpleasant subject. This study examines whether mathematics remains scary today. Previous research has limitations, particularly in terms of why primary school students have negative perception of mathematics. This study uses a descriptive qualitative design supported by quantitative data to obtain more in-depth results. The subjects of this study were 153 fifth-grade students from nine primary schools in the city of Palu, selected at random. Data were collected via a questionnaire, and responses were categorized as positive or negative. Based on this, 109 students (71%) gave negative responses, namely "mathematics has a lot of formulas", "mathematics is difficult", "mathematics is scary", and "mathematics is boring". Meanwhile, 44 other students (29%) gave positive responses, namely "mathematics is challenging" and "mathematics is enjoyable". Subsequently, six participants were selected who were representatives of each type of response to be interviewed. Data credibility was tested using the member check technique. Then, it was analyzed using three stages, namely data condensation (summarizing and connecting meaning between data), data presentation (displaying data in tables and descriptions) and drawing conclusions (connecting data with theory, data categorization, and data interpretation). The results of this study indicate that many primary school students still find mathematics intimidating. This perception is driven by two factors: the nature of mathematics and the way it is taught. This situation necessitates the continued development of learning strategies that can shift students' perceptions from negative to positive.